ANALISIS KELAYAKAN FINANSIAL PENGELOLAAN DAN PENGGUNAAN TRAKTOR RODA DUA (HAND TRAKTOR) DI KABUPATEN SAMBAS (Studi Kasus pada UPJA Penerima Bantuan Traktor Roda Dua Tahun 2015) - HERIYANSAH, HERIYANSAH; MUANI, ANI; ISYTAR, IBRAHIM (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2017)
UPJA (Usaha Pelayanan Jasa Alsiantan) as economic organization in rural area, which moves in the management and service, has purpose to get profit (profit making), managed based on economic scale, and market oriented. The purpose of this present research are: 1) Knowing the financial appropriateness of soil tillage service using the hand tractor, and 2) Knowing the comperation of the farmers’ income with land soil tillage (Olah Tanah) system (OT) that using hand tractor and the farmers’ income without soil tillage (Tanpa Olah Tanah) system (TOT). The present research that involved nine UPJA, 45 farmers using land maintenance service and 45 farmers whom not using land maintenance service, that spread out in five Sub-district in Sambas district, that are selakau, Selakau Timur, Pemangkat, Tebas an Jawai Sub-district. The data analyzed by two analysis tools that are: 1. The financial analysis with assessment indicators that an Net Present Value, Internal Rate of Return, Net Benefit Cost Ratio, and Sensitivity Analysis. 2. The t-Test analysis.